Diversity and endemism of Peruvian mammals - Pacheco, Víctor (2009)
We present an annotated list for all land, aquatic and marine mammals known to occur in Peru and their distribution by ecoregions. We also present species conservation status according to international organizations and the legal conservation status in Peru. At present, we record 508 species, in 13 orders, 50 families, and 218 genera, making Peru the third most diverse country with regards to mammals in the New World, after Brazil and Mexico, and the fifth most diverse country for mammals in the World. This diversity includes 40 didelphimorphs, 2 paucituberculates, 1 manatee, 6 cingulates, 7 pilosa, 39 primates, 162 rodents, 1 rabbit, 2 soricomorphs, 165 bats, 34 carnivores, 2 perissodactyls, and 47 cetartiodactyls. Bats and rodents (327 species) represent almost two thirds of total diversity (64%) for Peru. Five genera and 65 species (12.8%) are endemics to Peru, with the majority of these being rodents (45 species, 69,2%). Most of the endemic species are restricted to the Yungas of the eastern slope of the Andes (39 species, 60%) followed by Selva Baja (14 species, 21.5%). The taxonomic status of some species is commented on, when those depart from accepted taxonomy. The marsupial Marmosa phaea; the rodents Melanomys caliginosus, M. robustulus, and Echinoprocta rufescens; the shrew Cryptotis equatoris; the bats Anoura fistulata, Phyllostomus latifolius, Artibeus ravus, Cynomops greenhalli, Eumops maurus, and Rhogeessa velilla; and the carnivore Nasuella olivacea are first records of species occurrence in Peru. Finally, we also include a list of 15 non-native species.